2021
DOI: 10.1590/1413-82712021260411
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Development of Gifted Students: Comparative Study About Overexcitabilities

Abstract: The aim of this study was to compare gifted, with academic and artistic talent, and non-gifted students regarding overexcitability, as well as to investigate the perceptions of teachers from a specialized educational program for the gifted about their students’ emotional development. The study included 150 students and six teachers. As instruments, we used participants characterization questionnaires, an overexcitability scale and a semi-structured interview script. Data were analyzed using inferential statist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Among the scales used by these studies, as listed in Table 1, are Motor Test Battery (Krombholz, 2018), Online Short Spatial Ability Battery (OSSAB) (Budakova et al, 2021), and Battery of Intellectual and Creative Evaluation -Children's Version (BAICI) (Wechsler et al, 2022). Three studies used scales that focus on the characteristics of gifted students (Zaia et al, 2018;Jawabreh et al, 2022;de Sousa & Fleith, 2021). Some studies used self-report measures, such as the Science Self-Regulation Scale (Nacaroglu et al, 2021); the Pictorial Scale for Perceived Competence and Social Acceptance and the Behavioral Academic Self-Esteem Scale (Papadopoulos, 2021); and the Big Three Perfectionism Scale and the Rosenberg Self-Esteem Scale (Alshurman et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the scales used by these studies, as listed in Table 1, are Motor Test Battery (Krombholz, 2018), Online Short Spatial Ability Battery (OSSAB) (Budakova et al, 2021), and Battery of Intellectual and Creative Evaluation -Children's Version (BAICI) (Wechsler et al, 2022). Three studies used scales that focus on the characteristics of gifted students (Zaia et al, 2018;Jawabreh et al, 2022;de Sousa & Fleith, 2021). Some studies used self-report measures, such as the Science Self-Regulation Scale (Nacaroglu et al, 2021); the Pictorial Scale for Perceived Competence and Social Acceptance and the Behavioral Academic Self-Esteem Scale (Papadopoulos, 2021); and the Big Three Perfectionism Scale and the Rosenberg Self-Esteem Scale (Alshurman et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Most samples in the studies were students as shown in Figure 2: (Dori et al, 2018;Zaia et al, 2018;Vogelaar et al, 2019;Tushnova, 2020;Al-Gaseem et al, 2020;Nacaroglu et al, 2021;Alshurman et al, 2021;Ewies et al, 2021;Rosa et al, 2022;Wechsler et al, 2022;Pezzuti et al, 2022). Some studies included samples from among students and teachers (Sorrentino, 2019;de Sousa & Fleith, 2021). A study sampled 263 mothers and 90 children in the Czech Republic (Jabůrek et al, 2021).…”
Section: Type Of Samplementioning
confidence: 99%
See 1 more Smart Citation
“…These studies defined sensitivity differently than the definition of SPS in the present study or included specific components but showed considerable overlap with SPS. Best known are Dabrowski’s (1964) overexcitabilities (OEs), which are often related to giftedness (e.g., Alias et al, 2013; Mendaglio, 2022; Sousa & Fleith, 2022). SPS shares some characteristics with OEs, but these constructs are not identical, as illustrated in Table 1.…”
Section: Sps As a Characteristic Of Giftedness?mentioning
confidence: 99%